Discretionary power and accountability: a perspective of new public management / Ahmad Faiz Yaakob ... [et al.] - Yaakob, Ahmad Faiz; Salleh, Asri; Zakaria, Jazimin; Che Mohd Razali, Che Hamdan (2012)
The effectiveness of administrative reforms cannot be understood well without acknowledging the boundary of power between politics (politicians) and administration (administrators). Paradoxically, the separation of politics from public administration has led to the search of a new form of political control and the mechanisms to make political elites close to management and vice versa. Classical Public Administration did not augur well with this need. But, this was made possible with the introduction of a new concept of new public management. This paper provides an overview of the arguments relating to the effects of the new concept on bureaucrats and their relationships with politicians. The objective is to study the extent to which administrative reforms affect senior civil servants as a result of reforms being introduced into the public sector. The paper believes that reforms, if done in phases, along with the efforts to create responsive bureaucracy are achievable through substantial increase in political control.